Case Studies of Technology for Adults with Multiple Disabilities to Make Telephone Calls Independently. Issue 1 (August 2014) - Lancioni, Giulio E.; O'Reilly, Mark F.; Boccasini, Adele; Martire, Maria L. La; Singh, Nirbhay N.; Sigafoos, Jeff; Lang, Russell
Recent literature has shown the possibility of enabling individuals with multiple disabilities to make telephone calls independently via computer-aided telephone technology. These two case studies assessed a modified version of such technology and a commercial alternative to it for a woman and a man with multiple disabilities, respectively. The modified version used in Study 1 (a) presented the names of the persons available for a call and (b) reminded the participant of the response she needed to perform (i.e., pressing a microswitch) if she wanted to call any of those names/persons. The commercial device used in Study 2 was a Galaxy S3 (Samsung) equipped with the S-voice module, which allowed the participant to activate phone calls by uttering the word 'Call' followed by the name of the persons he wanted to call. The results of the studies showed that the participants learned to make phone calls independently using the technology / device available. Implications of the results are discussed.